Liver Research and Clinical Management 2018
DOI: 10.5772/intechopen.72883
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Hepatocellular Carcinoma Related to Aflatoxins: An Update

Abstract: Hepatocellular carcinoma (hepatocarcinoma) is a major type of primary liver cancer and one of the most frequent human malignant neoplasms. Aflatoxins are I-type chemical carcinogen for hepatocarcinoma. Increasing evidence has shown that hepatocarcinoma induced by aflatoxins is the result of interaction between aflatoxins and hereditary factor. Aflatoxins can induce DNA damage including DNA strand break, adducts formation, oxidative DNA damage, and gene mutation and determine which susceptible individuals featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 80 publications
3
15
0
Order By: Relevance
“…Our results exhibited HCC tumor samples from high AFB1 exposure areas have an average adduct amount of 2.27 AE 1.09 μmol/mol DNA. Supporting our findings, several studies from high AFB1 exposure areas Nanning and Tiandong, China, have also shown the similar level of DNA adducts [4,5,26,27,37,39,45]. Taken together, the amount of AFB1-DNA adducts should be able to reflect the hepatic toxic potential of AFB1.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results exhibited HCC tumor samples from high AFB1 exposure areas have an average adduct amount of 2.27 AE 1.09 μmol/mol DNA. Supporting our findings, several studies from high AFB1 exposure areas Nanning and Tiandong, China, have also shown the similar level of DNA adducts [4,5,26,27,37,39,45]. Taken together, the amount of AFB1-DNA adducts should be able to reflect the hepatic toxic potential of AFB1.…”
Section: Discussionsupporting
confidence: 89%
“…Aflatoxin B1 (AFB1) is an important type I chemical toxicant mainly produced by the toxigenic strains of Aspergillus flavus (A. flavus) and Aspergillus parasiticus (A. parasiticus) [1,2]. This carcinogen is often taken into human body via contaminating human foods such as nuts and cereals and displays its toxic effects, especially hepatic toxicity [1][2][3][4][5][6][7][8]. AFB1-induced hepatic effects consist of acute toxic damages (such as severe DNA damage, severe liver degeneration and necrosis, and the failure of hepatic function) and chronic cumulative damages (such as a series of cumulative DNA damage, slight hepatocellular degeneration and necrosis, chronic inflammation, liver cirrhosis, and liver cancer) [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that aforementioned HBV infection and AFB1 exposure are two major causes for Guangxiese HCC, we questioned whether there were interactive effects between causes and ADAMTS4 SNPs and accomplished a series of joint analyses based on the combination of ADAMTS4 genotypes and causes (Table ). Results showed that these individuals with both positive status of causes and risk genotypes would face higher risk for HCC.…”
Section: Resultsmentioning
confidence: 99%
“…Aflatoxin B1 (AFB1) is a knowledge I-type chemical carcinogen for primary hepatocellular carcinoma (PHCC) [1][2][3]. This carcinogen is mainly produced by Aspergillus parasiticus and Aspergillus flavus and often found in crops and food (including maize, nuts, and beans), which are raised in the areas with humid and hot environment [1,4,5].…”
Section: Introductionmentioning
confidence: 99%